Methodological approaches to evaluating the effectiveness of investment projects ("Journal "U". Economy. Management. Finance.", 2024)
The article discusses methodological approaches to assessing the effectiveness of investment projects. Analysis of the effectiveness of investment projects is an important tool for choosing a project. In a market economy, there are many investment opportunities. A set of tools is used to accurately analyze the effectiveness of projects. They ensure the reliability of information and allow you to evaluate the effectiveness of each project.The article analyzes the impact of various factors on the effectiveness of investment projects. This helps to take into account the risks and unpredictability associated with the implementation of projects. The article also discusses the criteria for choosing investment projects, such as profitability, payback, stability and social significance. This allows us to identify the most promising projects that can bring significant benefits to society and investors. The article also suggests improving the methodology for evaluating the effectiveness of investment projects. This may include the use of modern technologies and analytical methods, as well as taking into account the specifics of the industry and the region. At the end of the article, it can be concluded that evaluating the effectiveness of investment projects is crucial for sustainable economic growth. This process helps to make informed decisions about project financing, reduce risks and increase the competitiveness of a country or region.
Keywords: efficiency of the enterprise; assessment of the effectiveness of the investment project; net present value; payback period; rate of return; profitability